PERBANKAN DAN PENINGKATAN LITERASI SERTA INKLUSI KEUANGAN - Muhtar (MANAJEMEN DEWANTARA, 2023)
Financial inclusion is widely regarded as a key towards reducing inequality. Providing a better access to finance helps to reduce poverty by granting more equal opportunity to grow. Therefore, to promote a more inclusive economic growth, G20 countries establish principles for innovative financial inclusion to share and promote together the development of inclusive finance. This study reviews previous both empirical and theoritical literatures to provide more evidences how the current body of literature has examined financial inclusion. Based on the previous literature, financial inclusion is determined not only by the lower cost but also distance to service, legal protection and political stability. Hence, providing wider range of services, a better legal protection and political stability is necessery particularly to promote more inclusive economic growth which is associated to financial inclusion. Keywords: Banking, Financial inclusion, Literate